1983
DOI: 10.1159/000176627
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Diets Deficient or Excessive in Selenium by Syrian Hamsters

Abstract: Syrian hamsters were fed torula yeast (TY) diets with 8 selenium (Se) supplement levels (0.0-10.0 ppm Se as sodium selenite) or casein (C) diets with 5 supplement levels (0.0-5.0 ppm Se as sodium selenite) for 25 weeks. Whole blood Se, plasma glutathione peroxidase (GSH-Px) activity and erythrocyte GSH-Px activity were measured after 5, 10, 15 and 25 weeks. At 25 weeks hematology was examined and tissue samples analyzed for Se and evaluated for histopathological lesions. While survival was not influenced by di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Approximately 98% of blood GSH-PX activity in dairy cattle is associated with erythrocytes [4] and the erythrocytic GSH-PX activity correlates highly with the level of selenium in blood [2,34], The esti mation of erythrocytic GSH-PX activity in the present study revealed a significant in crease of this enzyme in organic and inor ganic toxicity, which is in accordance with the observations of other workers [2,3,13,17,20,33,34]. Though significant increase in erythrocyte GSH-PX was observed on the 20th day of experimental feeding of seleni um-rich feed, the maximum activity was no ticed on 30-40 days.…”
Section: Discussionsupporting
confidence: 91%
“…Approximately 98% of blood GSH-PX activity in dairy cattle is associated with erythrocytes [4] and the erythrocytic GSH-PX activity correlates highly with the level of selenium in blood [2,34], The esti mation of erythrocytic GSH-PX activity in the present study revealed a significant in crease of this enzyme in organic and inor ganic toxicity, which is in accordance with the observations of other workers [2,3,13,17,20,33,34]. Though significant increase in erythrocyte GSH-PX was observed on the 20th day of experimental feeding of seleni um-rich feed, the maximum activity was no ticed on 30-40 days.…”
Section: Discussionsupporting
confidence: 91%
“…Following the acclimatization period, hamsters were fed for three wk one of four diets (Table 1) which consisted of: i) Control (CT) containing formulated basal requirements of α-Toc and Se; ii) CT + α-toc (67 IU all-racemic α-tocopheryl acetate/kg diet); iii) CT + Se (3.4 mg Se/kg diet); iv) CT + α-Toc (67 IU all-racemic α-tocopheryl acetate/kg diet) + Se (3.4 mg Se/kg diet). The pharmacological supplemental level of Se (3.4 ppm/kg diet) was chosen to be equivalent to two-thirds of the non-toxic 5 ppm Se/kg diet dose fed previously to Syrian hamsters for 25 wk 50. Subacute toxicity of Se has been tested in previous work, which found levels of dietary Se up to 10 ppm to be non-toxic to Syrian hamsters 51,52.…”
Section: Methodsmentioning
confidence: 99%
“…The pharmacological supplemental level of Se (3.4 ppm/kg diet) was chosen to be equivalent to two-thirds of the non-toxic 5 ppm Se/kg diet dose fed previously to Syrian hamsters for 25 wk. 50 Subacute toxicity of Se has been tested in previous work, which found levels of dietary Se up to 10 ppm to be non-toxic to Syrian hamsters. 51,52 The levels of α-Toc in the basal diet were chosen based on National Research Council (NRC) recommendations for the hamster of 27 IU all-racemic α-tocopheryl acetate/kg diet (10 tocopherol equivalents = 10 mg all-racemic α-tocopherol = 15 IU).…”
Section: Materials and Methods Experiments 1-animals Diets And Samplmentioning
confidence: 99%
“…Blood and tissue Se concentrations were [34,35], Recent studies [36] in our laboratory using several dietary Se levels between 0 and 10 ppm for 25 weeks have demonstrated that plasma and erythrocyte GSH-Px activity in hamsters increases with Se, with peak activ ity at Se levels of 5-10 ppm. In this study, the highest GSH-Px activity was also observed in the 10 ppm Se-fed group.…”
Section: Discussionmentioning
confidence: 91%